Inside story food packaging - Leign, Richard; Video Education Australasia (Bendigo , Vic : Video Education Australia, 2003)
Three self-contained stories look at materials , innovation and environmental issues of food packaging
Editor , Joel De Courey Browne ; Graphic , Clare Scopes ; Camera , Patrick Burns and Richard Leign ; Sound , Wayne Martin ; Executive producer , Mark McAuliffe
Newdesk : Eleanor Handley , Jim Pidgeon
Keywords: Food -- Packaging; Food industry and trade